Surviving at the extreme: Chimpanzee ranging is not restricted in a deforested human‐dominated landscape in Uganda. (3rd October 2020) - McLennan, Matthew R.; Hintz, Benjamin; Kiiza, Vicent; Rohen, Jacqueline; Lorenti, Georgia A.; Hockings, Kimberley J.
Abstract: Endangered wildlife increasingly inhabits human‐dominated landscapes outside protected areas. Large‐bodied mammals require large spaces, and their ranging may be especially impacted by landscape modifications including farming, road development and urbanisation. We studied the Wagaisa community of chimpanzees ( Pan troglodytes ) in Uganda, which inhabit a landscape characterised by high human population density, widespread deforestation, and rapid agricultural and infrastructural development. We aimed to assess whether this dynamic, fragmented environment constrains the chimpanzees' ranging, and to identify critical habitat patches to aid their conservation. During March–May 2018, we assessed range use from locations of direct observations and indirect signs, corroborated by longer‐term behavioural monitoring of the chimpanzees (June 2018–December 2019). No evidence of limited ranging was found. The Wagaisa chimpanzees used an area measuring ≥ 43 km 2 (100% MCP) and ranged extensively in the anthropogenic matrix. Most frequently used parts of the range ('core habitat areas') centred around small (5–20 acres), widely dispersed remnant forest patches and exotic eucalyptus plantations. Forty per cent of chimpanzee nests were constructed in eucalyptus trees, suggesting a behavioural adjustment to landscape changes. Actions to facilitate conservation of these 'village chimpanzees' and others surviving in transformed human‐dominated habitat need not conflict with the sustainable development of the region. Résumé: Les espèces sauvages en voie de disparition habitent de plus en plus les environnements dominés par l'homme en dehors des zones protégées. Les mammifères de grande taille nécessitent de grands espaces et leur répartition peut être particulièrement affectée par les modifications de l'environnement, notamment l'agriculture, le développement des routes et l'urbanisation. Nous avons étudié la communauté de chimpanzés Wagaisa ( Pan troglodytes ) en Ouganda, qui habitent un environnement caractérisé par une forte densité de population humaine, une déforestation généralisée et un développement agricole et infrastructurel rapide. Notre objectif était de déterminer si cet environnement dynamique et fragmenté affectait la répartition des chimpanzés, et d'identifier des parcelles d'habitat essentiel pour faciliter leur conservation. Entre mars et mai 2018, nous avons étudié l'utilisation des zones de répartition au sein des sites d'observation directe et de signes indirects. Nous avons corroboré notre étude par la surveillance comportementale à plus long terme des chimpanzés (de juin 2018 à décembre 2019). Aucune preuve de limitation de répartition n'a été trouvée. Les chimpanzés Wagaisa ont utilisé une zone mesurant ≥43 km 2 (100% MCP) et se situaient principalement dans la matrice anthropique. Les zones les plus fréquemment utilisées de l'aire de répartition (« zones d'habitat principal ») convergeaient autour de petites parcelles forestières résiduelles (de 2 à 8 hectares) largement dispersées et de plantations d'eucalyptus exotiques. Quarante pour cent des nids de chimpanzés ont été construits dans des eucalyptus, ce qui suggère un ajustement comportemental aux changements de l'environnement. Les actions visant à faciliter la conservation de ces « chimpanzés villageois » et des autres survivant dans un habitat transformé dominé par l'homme ne s'opposent pas nécessairement au développement durable de la région.